The effect of auditor’s reputation and auditor’s opinion on stock prices: Evidence from IDX main board index - Valentine Siagian (Universitas Hayam Wuruk Perbanas, 2023)
This paper examines the effect of the auditor reputation and the auditor's opinion on the stock prices of the firm in the following year from IndonesiaÂ Main Board Index for the period of 2016 to 2020. This research aims to study the importance of the auditor's reputation and the opinion given to the value of the firm by their stock prices movements in the following year.Â Regression analysis was applied with control variable and year fixed effectÂ to find out whether or not the reputation of the auditor and the opinion givenÂ by the auditor could affect the stock prices of the firm in each sample year.Â The result shows that auditor's reputation does affect the stock prices in theÂ following year which means choosing BIG4 CPA firm will increase stock prices in the following year, while auditor's opinion does not affect the stockÂ prices of the firm in the following year.